Reduced Expression of Endothelial Cell Markers after Long-term Transdermal Hormone Replacement Therapy in Women with Coronary Artery Disease - Seljeflot, Ingebjørg; Arnesen, Harald; Hofstad, Ann-Elin; Os, Ingrid (Thrombosis and Haemostasis, 2000)
The effects of 12 months hormone replacement therapy (HRT) on biochemical markers associated with endothelial function were studied in 98 postmenopausal women with CAD, who were randomized to transdermal HRT or a control group.A significant reduction in the levels of von Willebrand factor in the HRT-group compared to controls was seen after 3 months, maintained after 12 months (p <0.001). Significant reduction in the HRT-group compared to controls was also seen in VCAM-1 after 3 months, sustained after 12 months (p = 0.013 and p = 0.045, respectively), and E-selectin was reduced by about 20% after 3 months on HRT, the reduction being statistically significant after 12 months (p <0.001). Significantly reduced levels of ICAM-1 were also seen after 12 months (p = 0.048). No effects could be observed on tPA-antigen or thrombomodulin.The reduction in procoagulant and proinflammatory markers of endothelial function after long-term transdermal HRT could indicate a beneficial effect on the endothelium and thus a potentially modulating effect on the progression of atherosclerosis in women with CAD.
Keywords: Hormone replacement therapy; endothelial cell markers; atherosclerosis; procoagulant activity; inflammation